Aplikasi PGPR Akar Bambu dan Akar Putri Malu dalam Mengurangi Intensitas Serangan Aphis gosypii pada Tanaman Cabai (Capsicum annum L.) - Safitri, Betari; Febria, Dila; Yeni, Yeni; Prajaka, Nanang Wahyu (Savana Cendana, 2024)
Plant growth promoting rhizobacter (PGPR) contains Rhizobacter which can fix free nitrogen found in nature, the nitrogen is converted into ammonia which is then distributed to plants. The aim of this research was to determine the effect of administering pgpr from two different bioactivator sources on the intensity of aphid attacks on chili plants. The experimental design used was a Completely Randomized Design (CRD) which consisted of two factors, namely the PGPR concentration of bamboo roots and mimosa roots, namely 0%, 25%, 50%, 75% and 100%. Each treatment was repeated 3 times with each experimental unit consisting of 4 curly chili plants of the Thunder 99 variety. Applications were carried out once a week during the vegetative period. Observations began at 1 WAP and once a week with the observation variables being the type of aphids and the intensity of aphid attacks on each plant during the vegetative period. The results obtained by administering PGPR bamboo roots and putrimalu roots were less effective because they were unable to suppress the intensity of aphid attacks on chili plants. Intensity of aphid attacks not different than control. The level of intensity of aphid attacks is directly proportional to the aphid population. PGPR that can relatively reduce the intensity of aphid attacks is bamboo root treatment with a concentration of 75%. A better PGPR bioactivator comes from bamboo roots rather than mimosa roots.